Travels and archaeology in South Chile - Bird, Junius Bouton, 1907-1982.; Bird, Margaret; Hyslop, John, 1945-1993. (Iowa City : University of Iowa Press, 1988)
"This is a remarkable book by one of the true geniuses in the field of anthropology during this century and one who provided valuable data for specialists in other disciplines as well."â€"H. M. Wormington"An engaging manuscript that should charm a broad audience."â€"Thomas F. Lynch"The field notes of Junius, and Peggy's diary, are valuable records of the excavations, artifacts, and interpretations of the best archaeologists to work in the southern tip of South America."â€"James G. GriffinJunius Bird's three great archaeological field achievementsâ€"at the Strait of Magellan in Chilean Patagoni.
Broken or "Cut" BoneDomestication of the Sloth; Summary of Evidence; Age of Remains; Two Additional Specimens; Editor's Postscript; Bibliography
Includes bibliographical references (pages 241-246).
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Bird, Junius Bouton, -- 1907-1982.; Bird, Junius B. -- 1907-1982.; Bird, Junius Bouton, -- 1907-1982; Indians of South America -- Chile -- Antiquities; Chile -- Antiquities; Peuples autochtones -- Chili -- Antiquités.; Chili -- Antiquités.; HISTORY; SOCIAL SCIENCE -- General; Antiquities; Indians of South America -- Antiquities; Chile; Reisebericht; Vor- und Frühgeschichte; Ausgrabung; Chile -- Süd; Indiens -- Chili -- Antiquités.; Chili -- Antiquités.; Chile -- Antiquitaes